Nano-modified ultrahigh-toughness concrete and preparation method thereof

By using nanomodification technology and basalt fiber re-adultiplexing in ultra-high toughness concrete, combined with thin layer tamping forming process, the problem of steam maintenance in the existing technology is solved, and the achievement of under natural maintenance conditions is achieved High-performance nanomodified ultra-high toughness concrete reduces cost and operational complexity.

CN119285286AActive Publication Date: 2025-01-10ROAD & BRIDGE INT CO LTD +1

Patent Information

Application Number
CN202411459245.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-10
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

Existing ultra-high toughness concrete requires steam curing to meet performance standards, the process is complex and economically expensive, and the lack of natural curing can achieve performance standards.

Method used

The preparation method of nanomodified ultra-high toughness concrete includes fine aggregate, water, water reducing agent, gelling material and nanosilica, steel fiber, glue ratio is 1.0, water glue ratio is 0.16, steel fiber doping The amount is 1.2-2.5%, and the amount of nano-silica dosage is 0.5-2%. The basalt fiber and thin layer tamping molding process treated with dispersed wetting agent is optimized. Achieve high performance under natural maintenance.

Benefits of technology

Under natural maintenance conditions, the mechanical properties and working properties meet the design and construction requirements, reducing costs, convenient operation, suitable for industrial production, avoiding the complexity and high costs of steam maintenance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285286A_ABST
    Figure CN119285286A_ABST
Patent Text Reader

Abstract

The invention provides nano-modified ultrahigh-toughness concrete and a preparation method thereof, and the nano-modified ultrahigh-toughness concrete is prepared from the following raw materials in parts by mass: 100-140 parts of fine aggregate, 8-18 parts of water and 2-4 parts of a water reducing agent, the cementing material comprises the following components in parts by weight: 10-20 parts of silica fume, 10-30 parts of superfine fly ash aluminosilicate fine matter and 50-80 parts of cement; wherein the water-binder ratio is 0.16; the volume mixing amount of the steel fibers is 1.2-2.5%, and the mixing amount of the nano silicon dioxide is 0.5-2%. According to the invention, the components of the ternary gel system and the doping amount of nano silicon dioxide are limited; the working performance and the mechanical performance of the ultrahigh-toughness concrete are greatly improved; the preparation method of the nano-modified ultrahigh-toughness concrete has the characteristics of low cost, convenience in operation, wide application scene and suitability for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of concrete, and more specifically, to a nano-modified ultra-high toughness concrete and a preparation method thereof. Background Art

[0002] In recent years, with the increasing requirements for bridge design and the increasingly complex use environment, the design of orthotropic steel bridge deck composite systems faces severe challenges. The steel-super-toughness concrete (STC) lightweight composite bridge deck structure design can improve the overall stiffness of the bridge deck system and effectively deal with problems such as fatigue cracking of steel bridge decks and pavement layer diseases. Among them, the STC layer is composed of raw materials such as cement, quartz sand, mineral admixtures, steel fibers, and water reducers. After coagulation and hardening, it has high strength, high toughness, and excellent durability. It can adapt to the situation of local stress concentration and large deformation of steel bridge decks, and has broad application prospects in the future bridge engineering industry. At present, a lot of research has been carried out in the field of the modification effect of nanomaterials on binary or ternary cementitious systems, mainly involving nano-SiO2, nano-TiO2, carbon nanotubes CNT, etc. Among them, Xu Peng et al. summarized and analyzed the effects of the characteristics, incorporation methods and dosage of nanomaterials such as nano-SiO2, nano-TiO2, carbon nanotubes (CNT) and graphene oxide (GO) on the functional modification performance of cement-based materials, and proposed the concept of multifunctional synergistic development of nano-modified cement-based materials. Wu et al. studied the reinforcing mechanism of UHPC by the incorporation of nano-SiO2 and nano-CaCO3, and found that the mechanical strength of UHPC first increased and then decreased with the incorporation of nano-SiO2 and nano-CaCO3, and the optimal incorporation was 1% and 3.2%, respectively. However, there is a lack of research on the modification of ultra-high toughness concrete by nano-SiO2.

[0003] The prior art discloses a method for preparing nano-silicon dioxide and steel fiber reinforced concrete, which includes: weighing aggregate, cement, water reducer, fly ash, water, nano-SiO2 and steel fiber; taking appropriate amount of nano-SiO2 and water reducer and adding them into water, stirring evenly and setting aside; after wetting the mixer, adding coarse aggregate and fine aggregate, stirring, then adding cement and fly ash, stirring, then uniformly mixing the steel fiber along the rotating direction of the mixer impeller, adding a mixture of nano-material, water reducer and part of water after stirring, stirring, adding the remaining water, stirring, and obtaining nano-silicon dioxide and steel fiber reinforced concrete. Although the modification of concrete by nano-SiO2 is involved, the modified ultra-high toughness concrete obtained by the above-mentioned preparation method containing nano-SiO2 requires steam curing to reach the performance standard; however, steam curing has the disadvantages of complex process, high economic cost, time-consuming and labor-intensive.

[0004] Therefore, there is an urgent need for an ultra-high toughness concrete that can meet performance standards through natural curing alone. Summary of the invention

[0005] In view of the above problems, an object of the present invention is to provide a nano-modified ultra-high toughness concrete and a preparation method thereof, so as to solve at least one of the above technical problems.

[0006] According to one aspect of the present invention, there is provided a nano-modified ultra-high toughness concrete.

[0007] The preparation raw materials include: fine aggregate, water, water reducing agent, cementitious material, steel fiber and nano-silicon dioxide; wherein the cementitious-to-brick ratio is 1.0 and the water-to-brick ratio is 0.16;

[0008] The volume content of steel fiber is 1.2-2.5%, and the mass content of nano silicon dioxide is 0.5-2%;

[0009] In terms of weight percentage, the cementitious materials include: 50% to 80% cement, 10% to 20% silica fume, 20% to 25% ultrafine fly ash aluminosilicate fine matter, and 5% to 10% viscosity reducer.

[0010] Further, preferably,

[0011] The invention also comprises basalt fibers treated with a dispersed sizing agent, wherein the volumetric dosage of the basalt fibers is 0.3-0.5%.

[0012] Further, preferably,

[0013] The dispersed wetting agent is water-soluble epoxy emulsion, KH550 and cation.

[0014] Further, preferably,

[0015] The fine aggregate is 10-20 mesh quartz sand and 70-140 mesh quartz sand in a mixing ratio of 3:2.

[0016] Further, preferably,

[0017] The dosage of the nano silicon dioxide is 1-2%.

[0018] Further, preferably,

[0019] The particle size of the nano silicon dioxide is 20 to 50 nm.

[0020] The present invention also protects a method for preparing nano-modified ultra-high toughness concrete, which is used to prepare the above-mentioned nano-modified ultra-high toughness concrete; the method comprises:

[0021] Add fine aggregate, cementitious material and dispersed pre-treated nano-silicon dioxide solution into a concrete mixer and mix evenly;

[0022] Add water and water reducing agent and mix well;

[0023] Steel fibers are evenly sprinkled to obtain nano-modified ultra-high toughness concrete.

[0024] Further, preferably,

[0025] It also includes the use of thin layer tamping during the casting process, including,

[0026] The obtained nano-modified ultra-high toughness concrete is poured from one end of the mold;

[0027] According to the preset thickness of each layer, pouring and smoothing are performed along the long side of the mold; wherein the thickness of each layer is 0.8 to 1.2 cm.

[0028] Further, preferably,

[0029] The dosage of nano silicon dioxide in the nano-modified ultra-high toughness concrete is 2%.

[0030] Further, preferably,

[0031] The steel fiber is a microfilament copper-plated steel fiber with a length of 14 mm and an equivalent diameter of 0.22 mm.

[0032] The above-mentioned nano-modified ultra-high toughness concrete preparation method according to the present invention is used for steel bridge deck pavement; by limiting the components of the ternary cementitious system and the dosage of nano-silicon dioxide; ultra-high toughness concrete with greatly improved working performance and mechanical properties is obtained; the nano-modified ultra-high toughness concrete for bridge deck pavement disclosed in the present invention is a cement-based composite material with better comprehensive performance obtained by three methods: nano-SiO2 modification, basalt fiber compounding, and molding process optimization. Different from the STC required by existing standards and specifications to adopt steam curing, the mechanical properties and working performance of the present invention under natural curing conditions can still meet the requirements of design and construction; the nano-modified ultra-high toughness concrete of the present invention can also meet the mechanical performance standards by natural curing; the nano-modified ultra-high toughness concrete preparation method of the present invention has the characteristics of low cost, convenient operation, wide application scenarios, and is suitable for industrial production.

[0033] In order to achieve the above and related purposes, one or more aspects of the present invention include features that will be described in detail later and are particularly pointed out in the claims. The following description and the accompanying drawings describe some exemplary aspects of the present invention in detail. However, these aspects indicate only some of the various ways in which the principles of the present invention can be used. In addition, the present invention is intended to include all of these aspects and their equivalents. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] By referring to the following description and claims in conjunction with the accompanying drawings, and with a more comprehensive understanding of the present invention, other objects and results of the present invention will become more apparent and easier to understand. In the accompanying drawings:

[0035] Figure 1 A flow chart showing a method for preparing nano-modified ultra-high toughness concrete according to the present invention; and

[0036] Figure 2 The actual comparison diagram of nano-modified ultra-high toughness concrete in various working conditions is shown;

[0037] Figure 3 CT images of ZB-4 nano-modified ultra-high toughness concrete under thin layer tamping and conventional pouring are shown.

[0038] The same reference numerals throughout the drawings indicate similar or corresponding features or functions. DETAILED DESCRIPTION

[0039] In the following description, for the purpose of illustration, in order to provide a comprehensive understanding of one or more embodiments, many specific details are set forth. However, it is apparent that these embodiments may also be implemented without these specific details. In other examples, for ease of describing one or more embodiments, known structures and devices are shown in the form of block diagrams.

[0040] Silica fume reacts with calcium hydroxide generated by cement hydration to form CSH gel with a single chemical composition. The addition of silica fume will cause a secondary pozzolanic reaction at an early age, consuming the amount of CH in the slurry and generating more CSH gel; the reason for the increase in strength is the pozzolanic effect and filling effect of silica fume. Silica fume can fill the pores of the slurry, increase the density, refine the pore structure, and have a micro-aggregate effect. At the same time, in mortar or concrete, silica fume can also improve the slurry-aggregate interface area.

[0041] The present invention mainly compares and analyzes the working performance and basic mechanical properties of concrete in various working conditions under different nano-SiO2 dosages, and compares and analyzes the flexural strength under two molding processes: thin layer tamping and conventional pouring, to obtain ultra-high toughness concrete with greatly improved working performance and mechanical properties.

[0042] In the prior art, quartz sand and polycarboxylic acid water reducer are mixed by microwave treatment, and quartz sand dissociates under microwave and acid to form nano-SiO2, so as to prepare nano-SiO2 dispersion; the present invention adopts a combination of physical and chemical methods for the dispersion of nanomaterials. Among them, the physical method is to physically disperse the nanomaterials at high speed by a mechanical stirrer. The rotation speed of the stirrer blade is 38000 rpm, the maximum capacity is 2.2L, and the stirring temperature is 40 degrees Celsius. The chemical method is to add a surfactant, that is, sodium hexametaphosphate is added to the mixed solution when dispersing the nanomaterials. The present invention is to make up for the disadvantages in natural curing strength, and improve the comprehensive performance of STC by means of composite fiber, nano-enhancement, and molding process optimization; thereby realizing the nano-modified ultra-high toughness concrete ratio under natural curing, and combining with a special preparation process and thin layer tamping, the technical effect of the strength required by the specification can be achieved.

[0043] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0044] The nano-modified ultra-high toughness concrete material of the present invention is a cement-silica fume-ultrafine fly ash aluminosilicate fine matter-viscosity reducer multi-component cementitious system concrete material. In each cubic meter of concrete, the total mass of the cementitious material is 1066kg, the proportion of the cementitious material to the aggregate, i.e., the cement-to-aggregate ratio, is 1.0, the proportion of water to the cementitious material, i.e., the water-to-binder ratio, is 0.16, the amount of the polycarboxylate water-reducing agent accounts for 2% to 3% of the mass of the cementitious material, the amount of the steel fiber accounts for 1.2% to 2.5% of the total volume of the concrete material, the amount of the basalt fiber accounts for 0.3% to 0.5% of the total volume of the concrete material, and the amount of the nano-silica accounts for 0.5% to 2% of the mass of the cementitious material. The cementitious material is recorded by weight percentage as follows: 50% to 80% of cement, 10% to 20% of silica fume, 20% to 25% of the ultrafine fly ash aluminosilicate fine matter, and 5% to 10% of the viscosity reducer. Since the ultrafine fly ash aluminosilicate fine material with a SiO2 content of 56.5% has a small particle size, a spherical shape, and a ball effect; in addition, the viscosity reducer has a fluidity ratio of 105%, a viscosity ratio of 55%, and 7d and 28d activity indexes of 75% and 90% respectively; in order to solve the problem of low fluidity caused by low water-binder ratio, the ultrafine fly ash aluminosilicate fine material and viscosity reducer are used to achieve the effect of improving the fluidity of concrete.

[0045] Example 1

[0046] Figure 1 A flow chart of a method for preparing nano-modified ultra-high toughness concrete according to the present invention is shown.

[0047] like Figure 1As shown, S110, fine aggregate, cementitious material and dispersed pre-treated nano-silicon dioxide solution are added into a concrete mixer and stirred evenly.

[0048] Nano-modified ultra-high toughness concrete includes, by weight, the following preparation raw materials:

[0049] 100-140 parts of fine aggregate, 8-18 parts of water, 2-4 parts of water reducer; cementitious materials: 10-20 parts of silica fume, 10-30 parts of ultrafine fly ash aluminosilicate fine matter, 50-80 parts of cement; wherein, the water-cement ratio is less than 0.2; the dosage of nano silicon dioxide is 0.5-2%.

[0050] The addition of silica fume, an ultrafine active mineral admixture, gives it a good micro-powder filling effect, reduces the pore size and porosity through chemical reaction, and optimizes the internal pore structure of the system.

[0051] The fine aggregate is quartz sand of 10-20 mesh and quartz sand of 70-140 mesh in a mixing ratio of 3:2. The dosage of the nano-silicon dioxide is 1-2%. The particle size of the nano-silicon dioxide is 20-50 nm. By removing the coarse aggregate, the maximum particle size of the fine aggregate is limited to no more than 300 μm, thereby improving the uniformity of the aggregate. And by optimizing the grading of the fine aggregate, the closest packing is achieved as much as possible to improve the density of the system.

[0052] S120. Add water and water reducing agent and mix well.

[0053] The water reducing agent is STC special polycarboxylic acid series high efficiency water reducing agent, and its water reducing rate can reach more than 35%; the mixing water is ordinary laboratory tap water.

[0054] S130, evenly spread steel fibers to obtain nano-modified ultra-high toughness concrete.

[0055] Among them, the volume content of steel fiber is 1.2-2.5% (external addition). The length of steel fiber is 13mm, the equivalent diameter is 0.2mm, and the aspect ratio is 65. Specifically, the fiber has the effect of strengthening, toughening and crack resistance on concrete. Concrete without steel fiber showed explosive destruction during the compression test due to the excessive energy accumulated inside, showing greater brittleness than ordinary concrete. The effect of fiber depends on the volume content of fiber and the fiber spacing. The finer the fiber and the higher the fiber content, the better the effect of strengthening the matrix; therefore, when the fiber volume ratio is the same, the strengthening, toughening and crack resistance effect of ultrafine fiber on ultra-high toughness concrete far exceeds the strengthening effect of ordinary steel fiber on ordinary concrete, thereby doubling the flexural strength.

[0056] By limiting the composition of the ternary cementitious system and the dosage of nano-silica, an ultra-high toughness concrete with greatly improved working performance and mechanical properties is obtained.

[0057] Preparation Example 1

[0058] S110, adding fine aggregate, cementitious material and dispersed pre-treated nano-silicon dioxide solution into a concrete mixer and stirring evenly; it should be noted that the nano-material is dispersed by high-speed stirring to avoid agglomeration;

[0059] Nano-modified ultra-high toughness concrete includes, by weight, the following preparation raw materials:

[0060] 10-20 mesh quartz sand 640 parts, 70-140 mesh quartz sand 427 parts; water 171 parts, water reducing agent 22 parts;

[0061] Ternary cementitious system: 107 parts of silica fume, 107 parts of ultrafine fly ash aluminosilicate fine matter, 853 parts of cement; the dosage of nano silicon dioxide is 0.5%. The physical properties of cement are shown in Table 1. The physical properties of nano silicon dioxide are shown in Table 2.

[0062] Table 1 Physical properties of cement

[0063]

[0064] Table 2 Physical performance indicators of nano-SiO2

[0065]

[0066]

[0067] S120. Add water and water reducing agent and mix well to ensure the fluidity of concrete.

[0068] The water reducing agent is STC special polycarboxylic acid series high efficiency water reducing agent, and its water reducing rate can reach more than 35%; the mixing water is ordinary laboratory tap water.

[0069] S130, evenly sprinkle the steel fibers and stir evenly to obtain ZB-1 nano-modified ultra-high toughness concrete.

[0070] The steel fiber is 117.75 parts by mass. The physical properties of the steel fiber are shown in Table 3.

[0071] Table 3 Physical properties of steel fibers

[0072]

[0073] The obtained ZB-1 nano-modified ultra-high toughness concrete was tested for working performance. After the test, the mixture was placed in a mold and covered with a film to retain water. The mold was removed two days later. The demolded specimens were placed in a natural curing environment, that is, at room temperature of about 20°C indoors, and a layer of plastic film was covered on the surface of the specimens. Watering was used for curing before reaching the test age. Mechanical properties tests were carried out after curing to 7d and 28d.

[0074] Preparation Example 2

[0075] S110, adding fine aggregate, cementitious material and dispersed pre-treated nano-silicon dioxide solution into a concrete mixer and stirring evenly; it should be noted that the nano-material is dispersed by high-speed stirring to avoid agglomeration;

[0076] Nano-modified ultra-high toughness concrete includes, by weight, the following preparation raw materials:

[0077] 10-20 mesh quartz sand 640 parts, 70-140 mesh quartz sand 427 parts; water 171 parts, water reducing agent 22 parts;

[0078] Ternary cementitious system: 213 parts of silica fume, 320 parts of ultrafine fly ash aluminosilicate fine matter, 533 parts of cement; the dosage of nano silicon dioxide is 1%. The physical performance indicators of cement and nano silicon dioxide are the same as those of Preparation Example 1.

[0079] S120. Add water and water reducing agent and mix well to ensure the fluidity of concrete.

[0080] The water reducing agent is STC special polycarboxylic acid series high efficiency water reducing agent, and its water reducing rate can reach more than 35%; the mixing water is ordinary laboratory tap water.

[0081] S130, evenly sprinkle the steel fibers and stir evenly to obtain ZB-2 nano-modified ultra-high toughness concrete.

[0082] The steel fiber is 235.5 parts by weight. The physical properties of the steel fiber are the same as those in Preparation Example 1.

[0083] The obtained ZB-2 nano-modified ultra-high toughness concrete was tested for working performance. After the test, the mixture was placed in a mold and covered with a film to retain water. The mold was removed two days later. The demolded specimens were placed in a natural curing environment, that is, at room temperature of about 20°C indoors, and a layer of plastic film was covered on the surface of the specimens. Watering was used for curing before the test age. Mechanical properties tests were carried out after curing to 7d and 28d.

[0084] Preparation Example 3

[0085] S110, adding fine aggregate, cementitious material and dispersed pre-treated nano-silicon dioxide solution into a concrete mixer and stirring evenly; it should be noted that the nano-material is dispersed by high-speed stirring to avoid agglomeration;

[0086] Nano-modified ultra-high toughness concrete includes, by weight, the following preparation raw materials:

[0087] 640 parts of 10-20 mesh quartz sand, 427 parts of 70-140 mesh quartz sand; 171 parts of water, 43 parts of water reducer;

[0088] Ternary cementitious system: 160 parts of silica fume, 160 parts of ultrafine fly ash aluminosilicate fine matter, 747 parts of cement; the dosage of nano silicon dioxide is 1.5%. The physical performance indicators of cement and nano silicon dioxide are the same as those of Preparation Example 1.

[0089] S120. Add water and water reducing agent and mix well to ensure the fluidity of concrete.

[0090] The water reducing agent is STC special polycarboxylic acid series high efficiency water reducing agent, and its water reducing rate can reach more than 35%; the mixing water is ordinary laboratory tap water.

[0091] S130, evenly sprinkle the steel fibers and stir evenly to obtain ZB-3 nano-modified ultra-high toughness concrete.

[0092] The steel fiber is 196.25 parts by weight. The physical properties of the steel fiber are the same as those in Preparation Example 1.

[0093] The obtained ZB-3 nano-modified ultra-high toughness concrete was tested for working performance. After the test, the mixture was placed in a mold and covered with a film to retain water. The mold was removed two days later. The specimens after demolding were placed in a natural curing environment, that is, at room temperature of about 20°C indoors, and a layer of plastic film was covered on the surface of the specimens. Watering was used for curing before reaching the test age. Mechanical properties tests were carried out after curing to 7d and 28d.

[0094] Preparation Example 4

[0095] S110, adding fine aggregate, cementitious material and dispersed pre-treated nano-silicon dioxide solution into a concrete mixer and stirring evenly; it should be noted that the nano-material is dispersed by high-speed stirring to avoid agglomeration;

[0096] Nano-modified ultra-high toughness concrete includes, by weight, the following preparation raw materials:

[0097] 640 parts of 10-20 mesh quartz sand, 427 parts of 70-140 mesh quartz sand; 171 parts of water, 43 parts of water reducer;

[0098] Ternary cementitious system: 160 parts of silica fume, 160 parts of ultrafine fly ash aluminosilicate fine matter, 747 parts of cement; the dosage of nano silicon dioxide is 2.0%. The physical performance indicators of cement and nano silicon dioxide are the same as those of Preparation Example 1.

[0099] S120. Add water and water reducing agent and mix well to ensure the fluidity of concrete.

[0100] The water reducing agent is STC special polycarboxylic acid series high efficiency water reducing agent, and its water reducing rate can reach more than 35%; the mixing water is ordinary laboratory tap water.

[0101] S130, evenly sprinkle the steel fibers and stir evenly to obtain ZB-4 nano-modified ultra-high toughness concrete.

[0102] The steel fiber is 196.25 parts by weight. The physical properties of the steel fiber are the same as those in Preparation Example 1.

[0103] The obtained ZB-4 nano-modified ultra-high toughness concrete was tested for working performance. After the test, the mixture was placed in a mold and covered with a film to retain water. The mold was removed two days later. The demolded specimens were placed in a natural curing environment, that is, at room temperature of about 20°C indoors, and a layer of plastic film was covered on the surface of the specimens. Watering was used for curing before reaching the test age. Mechanical properties tests were carried out after curing to 7d and 28d.

[0104] Preparation Example 5

[0105] S110, adding fine aggregate, cementitious material and dispersed pre-treated nano-silicon dioxide solution into a concrete mixer and stirring evenly; it should be noted that the nano-material is dispersed by high-speed stirring to avoid agglomeration;

[0106] Nano-modified ultra-high toughness concrete includes, by weight, the following preparation raw materials:

[0107] 640 parts of 10-20 mesh quartz sand, 427 parts of 70-140 mesh quartz sand; 171 parts of water, 43 parts of water reducer;

[0108] Ternary cementitious system: 160 parts of silica fume, 160 parts of ultrafine fly ash aluminosilicate fine matter, 747 parts of cement; the dosage of nano silicon dioxide is 2.5%. The physical performance indicators of cement and nano silicon dioxide are the same as those of Preparation Example 1.

[0109] S120. Add water and water reducing agent and mix well to ensure the fluidity of concrete.

[0110] The water reducing agent is STC special polycarboxylic acid series high efficiency water reducing agent, and its water reducing rate can reach more than 35%; the mixing water is ordinary laboratory tap water.

[0111] S130, evenly sprinkle the steel fibers and stir evenly to obtain ZB-5 nano-modified ultra-high toughness concrete.

[0112] The steel fiber is 196.25 parts by weight. The physical properties of the steel fiber are the same as those in Preparation Example 1.

[0113] The obtained ZB-5 nano-modified ultra-high toughness concrete was tested for working performance. After the test, the mixture was placed in a mold and covered with a film to retain water. The mold was removed two days later. The demolded specimens were placed in a natural curing environment, that is, at room temperature of about 20°C indoors, and a layer of plastic film was covered on the surface of the specimens. Watering was used for curing before reaching the test age. Mechanical properties tests were carried out after curing to 7d and 28d.

[0114] Preparation Example 6

[0115] S110, adding fine aggregate, cementitious material and dispersed pre-treated nano-silicon dioxide solution into a concrete mixer and stirring evenly; it should be noted that the nano-material is dispersed by high-speed stirring to avoid agglomeration;

[0116] Nano-modified ultra-high toughness concrete includes, by weight, the following preparation raw materials:

[0117] 640 parts of 10-20 mesh quartz sand, 427 parts of 70-140 mesh quartz sand; 171 parts of water, 32 parts of water reducer;

[0118] Ternary cementitious system: 107 parts of silica fume, 107 parts of ultrafine fly ash aluminosilicate fine matter, 853 parts of cement; the dosage of nano silicon dioxide is 2%. The physical performance indicators of cement and nano silicon dioxide are the same as those of Preparation Example 1.

[0119] S120. Add water and water reducing agent and mix well to ensure the fluidity of concrete.

[0120] The water reducing agent is STC special polycarboxylic acid series high efficiency water reducing agent, and its water reducing rate can reach more than 35%; the mixing water is ordinary laboratory tap water.

[0121] S130, evenly sprinkle steel fiber and basalt fiber treated with dispersed impregnating agent, stir evenly to obtain ZB-6 nano-modified ultra-high toughness concrete.

[0122] Among them, the steel fiber accounts for 172.7 parts by mass.

[0123] Basalt fiber is 8 parts;

[0124] The physical properties of basalt fiber are shown in Table 4; the surface impregnation agent composition of basalt fiber is shown in Table 5.

[0125] Table 4 Physical properties of basalt fiber

[0126]

[0127] Table 5 Composition of basalt fiber surface sizing agent

[0128]

[0129] The obtained ZB-6 nano-modified ultra-high toughness concrete was tested for working performance. After the test, the mixture was placed in a mold and covered with a film to retain water. The mold was removed two days later. The demolded specimens were placed in a natural curing environment, that is, at room temperature of about 20°C indoors, and a layer of plastic film was covered on the surface of the specimens. Watering was used for curing before reaching the test age. Mechanical properties tests were carried out after curing to 7d and 28d.

[0130] Preparation Example 7

[0131] S110, adding fine aggregate, cementitious material and dispersed pre-treated nano-silicon dioxide solution into a concrete mixer and stirring evenly; it should be noted that the nano-material is dispersed by high-speed stirring to avoid agglomeration;

[0132] Nano-modified ultra-high toughness concrete includes, by weight, the following preparation raw materials:

[0133] 640 parts of 10-20 mesh quartz sand, 427 parts of 70-140 mesh quartz sand; 171 parts of water, 32 parts of water reducer;

[0134] Ternary cementitious system: 213 parts of silica fume, 160 parts of ultrafine fly ash aluminosilicate fine matter, 693 parts of cement; the dosage of nano silicon dioxide is 2%. The physical performance indicators of cement and nano silicon dioxide are the same as those of Preparation Example 1.

[0135] S120. Add water and water reducing agent and mix well to ensure the fluidity of concrete.

[0136] The water reducing agent is STC special polycarboxylic acid series high efficiency water reducing agent, and its water reducing rate can reach more than 35%; the mixing water is ordinary laboratory tap water.

[0137] S130, evenly sprinkle steel fiber and basalt fiber treated with dispersed impregnating agent, stir evenly to obtain ZB-7 nano-modified ultra-high toughness concrete.

[0138] Among them, the steel fiber accounts for 157 parts by mass.

[0139] Basalt fiber is 13.2 parts;

[0140] The physical properties of the basalt fiber and the surface impregnation agent composition of the basalt fiber are the same as those in Preparation Example 6.

[0141] The obtained ZB-7 nano-modified ultra-high toughness concrete was tested for working performance. After the test, the mixture was placed in a mold and covered with a film to retain water. The mold was removed two days later. The demolded specimens were placed in a natural curing environment, that is, at room temperature of about 20°C indoors, and a layer of plastic film was covered on the surface of the specimens. Watering was used for curing before reaching the test age. Mechanical properties tests were carried out after curing to 7d and 28d.

[0142] Preparation Example 8

[0143] S110, adding fine aggregate, cementitious material and dispersed pre-treated nano-silicon dioxide solution into a concrete mixer and stirring evenly; it should be noted that the nano-material is dispersed by high-speed stirring to avoid agglomeration;

[0144] Nano-modified ultra-high toughness concrete includes, by weight, the following preparation raw materials:

[0145] 640 parts of 10-20 mesh quartz sand, 427 parts of 70-140 mesh quartz sand; 171 parts of water, 32 parts of water reducer;

[0146] Ternary cementitious system: 160 parts of silica fume, 160 parts of ultrafine fly ash aluminosilicate fine matter, 747 parts of cement; the dosage of nano silicon dioxide is 2%. The physical performance indicators of cement and nano silicon dioxide are the same as those of Preparation Example 1.

[0147] S120. Add water and water reducing agent and mix well to ensure the fluidity of concrete.

[0148] The water reducing agent is STC special polycarboxylic acid series high efficiency water reducing agent, and its water reducing rate can reach more than 35%; the mixing water is ordinary laboratory tap water.

[0149] S130, evenly sprinkle steel fiber and basalt fiber treated with dispersed impregnating agent, stir evenly to obtain ZB-8 nano-modified ultra-high toughness concrete.

[0150] Among them, the steel fiber accounts for 164.8 parts by mass.

[0151] basalt fiber is 10.57 parts;

[0152] The physical properties of the basalt fiber and the surface impregnation agent composition of the basalt fiber are the same as those in Preparation Example 6.

[0153] The obtained ZB-8 nano-modified ultra-high toughness concrete was tested for working performance. After the test, the mixture was placed in a mold and covered with a film to retain water. The mold was removed two days later. The demolded specimens were placed in a natural curing environment, that is, at room temperature of about 20°C indoors, and a layer of plastic film was covered on the surface of the specimens. Watering was used for curing before reaching the test age. Mechanical properties tests were carried out after curing to 7d and 28d.

[0154] Comparative Example 1

[0155] S110, adding fine aggregate, cementitious material and dispersed pre-treated nano-silicon dioxide solution into a concrete mixer and stirring evenly; it should be noted that the nano-material is dispersed by high-speed stirring to avoid agglomeration;

[0156] Nano-modified ultra-high toughness concrete includes, by weight, the following preparation raw materials:

[0157] 640 parts of 10-20 mesh quartz sand, 427 parts of 70-140 mesh quartz sand; 171 parts of water, 32 parts of water reducer;

[0158] Ternary cementitious system: 213 parts of silica fume, 160 parts of ultrafine fly ash aluminosilicate fine matter, 693 parts of cement; the dosage of nano silicon dioxide is 0%. The physical performance indexes of cement and nano silicon dioxide are the same as those of Preparation Example 1.

[0159] S120. Add water and water reducing agent and mix well to ensure the fluidity of concrete.

[0160] The water reducing agent is STC special polycarboxylic acid series high efficiency water reducing agent, and its water reducing rate can reach more than 35%; the mixing water is ordinary laboratory tap water.

[0161] S130, evenly sprinkle the steel fibers and stir evenly to obtain DB-1 nano-modified ultra-high toughness concrete.

[0162] The steel fiber is 196.25 parts by weight. The physical properties of the steel fiber are the same as those in Preparation Example 1.

[0163] The DB-1 nano-modified ultra-high toughness concrete was tested for its working performance. After the test, the mixture was placed in a mold and covered with a film to retain water. The mold was removed two days later. The specimens after demolding were placed in a natural curing environment, that is, at room temperature of about 20°C, and a layer of plastic film was covered on the surface of the specimens. Watering was used for curing before the test age. Mechanical properties tests were carried out after curing to 7d and 28d.

[0164] Comparative Example 2

[0165] S110, adding fine aggregate, cementitious material and dispersed pre-treated nano-silicon dioxide solution into a concrete mixer and stirring evenly; it should be noted that the nano-material is dispersed by high-speed stirring to avoid agglomeration;

[0166] Nano-modified ultra-high toughness concrete includes, by weight, the following preparation raw materials:

[0167] 640 parts of 10-20 mesh quartz sand, 427 parts of 70-140 mesh quartz sand; 171 parts of water, 32 parts of water reducer;

[0168] Ternary cementitious system: 213 parts of silica fume, 160 parts of ultrafine fly ash aluminosilicate fine matter, 693 parts of cement; the dosage of nano silicon dioxide is 3%. The physical performance indicators of cement and nano silicon dioxide are the same as those of Preparation Example 1.

[0169] S120. Add water and water reducing agent and mix well to ensure the fluidity of concrete.

[0170] The water reducing agent is STC special polycarboxylic acid series high efficiency water reducing agent, and its water reducing rate can reach more than 35%; the mixing water is ordinary laboratory tap water.

[0171] S130, evenly sprinkle the steel fibers, stir evenly to obtain DB-2 nano-modified ultra-high toughness concrete.

[0172] The steel fiber is 196.25 parts by weight. The physical properties of the steel fiber are the same as those in Preparation Example 1.

[0173] The DB-2 nano-modified ultra-high toughness concrete was tested for its working performance. After the test, the mixture was placed in a mold and covered with a film to retain water. The mold was removed two days later. The specimens after demolding were placed in a natural curing environment, that is, at room temperature of about 20°C indoors, and a layer of plastic film was covered on the surface of the specimens. Watering was used for curing before the test age was reached. Mechanical properties tests were carried out after curing to 7d and 28d.

[0174] Test Example 1

[0175] The obtained ZB-1 nano-modified ultra-high toughness concrete, ZB-2 nano-modified ultra-high toughness concrete, ZB-3 nano-modified ultra-high toughness concrete, ZB-4 nano-modified ultra-high toughness concrete, ZB-5 nano-modified ultra-high toughness concrete, ZB-6 nano-modified ultra-high toughness concrete, ZB-7 nano-modified ultra-high toughness concrete, ZB-8 nano-modified ultra-high toughness concrete and DB-1 nano-modified ultra-high toughness concrete, DB-2 nano-modified ultra-high toughness concrete were cast according to thin layer tamping and conventional one-time pouring technology to obtain flexural specimens, and the flexural strength performance test was carried out after curing to 7d and 28d age.

[0176] Thin-layer tamping refers to pouring the fresh concrete from one end of the mold, and pouring and smoothing it along the flow direction (the long side of the mold) with a thickness of about 1 cm per layer; one-time pouring refers to pouring the fresh concrete into the test mold at one time, smoothing and scraping off the excess slurry on the top layer, and vibrating it for 30 seconds using a non-magnetic vibration table.

[0177] According to GB / T 50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", the slump and expansion of the mixture are tested to test the working performance of the concrete mixture; according to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the mechanical properties of concrete mixtures are tested, and the compressive strength, splitting tensile strength and flexural strength of concrete specimens are tested. Among them, the specimen size for the compressive strength test and the splitting tensile strength test is a cube with a side length of 100mm, and the specimen size for the flexural strength test is 100mm×100mm×400mm.

[0178] The test results of slump, expansion, splitting tensile strength and compressive strength of each specimen are shown in Table 6.

[0179] Table 6 Slump, expansion, splitting tensile strength and compressive strength of flexural specimens

[0180]

[0181] By observing Table 6, it can be seen that with the increase of nano-SiO2 content, the working performance of STC decreases significantly, and the compressive strength and splitting tensile strength increase first and then decrease. This is because nano-silicon dioxide has a small particle size and a large specific surface area. When added to concrete, it can improve the pore structure of cement paste and generate denser hydration products inside the structure, thereby improving the mechanical strength and durability of the material. However, with the further increase of nano-material content, the fluidity of concrete deteriorates, and the fiber distribution is more affected by fluidity, which reduces the flexural strength of concrete.

[0182] Based on the experimental results, by limiting the composition of the ternary cementitious system and the dosage of nano-silica (nano-SiO2 dosage is 0.5%-2%), ultra-high toughness concrete with greatly improved working performance and mechanical properties was obtained. Among them, when the dosage of nano-SiO2 is 2%, the effect is the best. Compared with DB-1, the 28d flexural strength of ZB-4 is increased by about 21% when the thin layer is rammed.

[0183] In addition, compared with conventional casting, the flexural strength of STC under thin layer tamping is improved. For example, the 28d flexural strength of ZB-1 under thin layer tamping process is improved by about 23% compared with conventional casting process.

[0184] The multi-scale toughening of composite fiber can make the fiber play its own role at different stress levels in the concrete fracture process, achieve the purpose of step-by-step crack prevention, and further improve the toughness of STC. The surface of basalt fiber treated with dispersed impregnating agent is hydrophobic and has better dispersibility. It can replace a part of steel fiber and be added to ultra-high toughness concrete. Although it will cause the strength of concrete to decrease (the decrease is relatively small), the composite fiber has a significant improvement on the working performance and shrinkage resistance of STC, and the comprehensive performance is improved. It can be seen from Table 6 that the expansion of nano-modified ultra-high toughness concrete specimens is increased by about 10% and the strength is reduced by about 5% by composite fiber, and its fluidity is improved without reducing the strength.

[0185] Figure 2 The figure below is a comparison of the specimens formed by the thin layer tamping process and the conventional process. The specimen on the left is formed by the thin layer tamping process, and the specimen on the right is formed by the conventional process. Figure 2 It can be seen that the surface of the specimens after thin layer tamping is smoother and the hole defects are smaller, while the surface of the specimens formed by conventional processes is rough and has more defects. In addition, the holes of the DB-1 group specimens and the DB-2 group specimens whose nano-SiO2 content is not between 0.5% and 2.5% gradually become larger, and the defects also increase accordingly, and the two molding processes are obviously contrasted.

[0186] The flexural strength changes with the change of the dosage of nano-SiO2. Whether it is the thin-layer tamping process or the conventional process, the optimal range of the dosage of nano-SiO2 is 0.5%-2.5%. This is because the addition of nano-SiO2 can refine the internal pores of the concrete. At the same time, due to the nucleation effect of the nanoparticles, the loose CSH gel can be transformed into a mesh structure with nanoparticles as the core, forming a denser and stronger CSH gel, which significantly improves the strength of the matrix. However, when the dosage exceeds 2.5%, nano-SiO2 is difficult to disperse during the mixing process, resulting in agglomeration and unable to evenly fill the internal pores of the concrete. Instead, a weak area is formed at the cement stone and the interface, thereby reducing the strength of the matrix. And the flexural strength depends on the distribution of fiber to a great extent, and the distribution of steel fiber is affected by the fluidity of slurry. When the nano-SiO2 dosage increases from 0% to 0.5% (excluding 0.5%), the concrete fluidity is reduced but the change is not too large. The fiber distribution is less affected by the concrete fluidity, and due to the active effect of nano-SiO2, the concrete bonding strength is increased, so that the concrete flexural strength is improved under two molding processes. When the nano-SiO2 dosage increases to higher than 2.5%, the worse the concrete fluidity is, the greater the fiber distribution is affected by the fluidity, so that the concrete flexural strength is reduced under the conventional process. At this time, the best dosage of nano-SiO2 is 1%, but under the continuous improvement of nano-SiO2 to the concrete matrix strength and the situation of manual smoothing, the pore defects caused by the reduction of fluidity are reduced, so that the concrete flexural strength continues to improve under the thin layer tamping process. At this time, the best dosage of nano-SiO2 is 2%. When the dosage continues to increase beyond 2.5%, the slurry becomes very viscous and the concrete is difficult to flow. The influence of the molding process is limited, resulting in relatively poor fiber distribution, increased pore defects and weak areas inside the specimen, and reduced flexural strength of the concrete.

[0187] Test Example 2

[0188] CT images were obtained after thin layer tamping and conventional pouring of ZB-4 nano-modified ultra-high toughness concrete. Figure 3 a in the middle is a thin layer tamping; Figure 3 Figure b is conventional casting. Since the cross section of the steel fiber is circular, it appears as a white bright spot after binarization during the CT scanning process. If the shape of the white bright spot is closer to a circle and fuller, it means that the fiber is perpendicular to the CT ray direction, that is, parallel to the long axis of the specimen. At this time, the fiber tends to be distributed in the forward direction. Figure 3 It can be seen that the steel fibers tend to be distributed in the forward direction in the thin-layer tamping method, and the thin-layer tamping method helps to improve the performance of concrete, thereby improving the flexural strength.

[0189] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. A nano-modified ultra-high toughness concrete, characterized in that: The preparation raw materials include: fine aggregate, water, water reducing agent, cementitious material, steel fiber and nano-silicon dioxide; wherein the cementitious-to-brick ratio is 1.0 and the water-to-brick ratio is 0.16; The volume content of steel fiber is 1.2-2.5%, and the mass content of nano silicon dioxide is 0.5-2%; In terms of weight percentage, the cementitious materials include: 50% to 80% cement, 10% to 20% silica fume, 20% to 25% ultrafine fly ash aluminosilicate fine matter, and 5% to 10% viscosity reducer.

2. The nano-modified ultra-high toughness concrete according to claim 1, characterized in that: The invention also comprises basalt fibers treated with a dispersed sizing agent, wherein the volumetric dosage of the basalt fibers is 0.3-0.5%.

3. The nano-modified ultra-high toughness concrete according to claim 2, characterized in that: The dispersed wetting agent is water-soluble epoxy emulsion, KH550 and cation.

4. The nano-modified ultra-high toughness concrete according to claim 1, characterized in that: The fine aggregate is 10-20 mesh quartz sand and 70-140 mesh quartz sand in a mixing ratio of 3:

2.

5. The nano-modified ultra-high toughness concrete according to claim 1, characterized in that: The dosage of the nano silicon dioxide is 1-2%.

6. The nano-modified ultra-high toughness concrete according to claim 5, characterized in that: The particle size of the nano silicon dioxide is 20 to 50 nm.

7. A method for preparing nano-modified ultra-high toughness concrete, characterized in that: Used to prepare the nano-modified ultra-high toughness concrete according to claim 1; the method comprises: Add fine aggregate, cementitious material and dispersed pre-treated nano-silicon dioxide solution into a concrete mixer and mix evenly; Add water and water reducing agent and mix well; Steel fibers are evenly sprinkled to obtain nano-modified ultra-high toughness concrete.

8. The method for preparing nano-modified ultra-high toughness concrete according to claim 7, characterized in that: It also includes the use of thin layer tamping during the casting process, including, The obtained nano-modified ultra-high toughness concrete is poured from one end of the mold; According to the preset thickness of each layer, pouring and smoothing are performed along the long side of the mold; wherein the thickness of each layer is 0.8 to 1.2 cm.

9. The method for preparing nano-modified ultra-high toughness concrete according to claim 8, characterized in that: The basalt fiber has a density of 2.643 g / cm 3 , with a diameter of 17 microns.

10. The method for preparing nano-modified ultra-high toughness concrete according to claim 7, characterized in that: The steel fiber is a microfilament copper-plated steel fiber with a length of 14 mm and an equivalent diameter of 0.22 mm.

Citation Information

Patent Citations

  • Shrinkage-resistant ultrahigh-toughness concrete and preparation method thereof

    CN113955998A

Cited By

  • Multi-dimensional nano synergistic modified ultrahigh-strength ultrahigh-toughness concrete and preparation method thereof

    CN122403877A